Effect of board diversity on corporate governance structure and operating performance: evidence from the UK listed firms* - Alabede, James Oladapo (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study expands the model of corporate governance to incorporate moderating effect of board diversity. It also investigates the relationship between internal corporate governance structures and firm performance and how this relationship is moderated by the influence of board diversity. The data of the study, which were extracted from annual reports of the UK FTSE 350 firms, were treated statistically using OLS-moderating multiple regression analysis. The coefficients provide evidence that the proportion of outside directors, board size, board diversity are significantly positively related to operating performance (ROA). The empirical evidence also indicates that the moderating effect of board diversity strengthens the relationship between outside directors and operating performance as well as between board size and operating performance. By implication, the result suggests that Agency Theory must explicitly indicate that board diversity plays important moderating role in corporate governance.